Dual polygonal slit square patch with defected ground plane for tri band operation. Issue 5 (May 2017) - Rakesh Kumar, P.; Satya Prasad, K.; Guruva Reddy, A.
ABSTRACT: A novel triple‐band square shaped microstrip planar antenna for IMAT2000&WiMAX operation is proposed and investigated. Single probe fed antenna consists of dual polygonal slits cut on top area of the radiating metallic layer and asymmetric dual H‐shaped defected ground structure etched on the bottom area of the metallic ground plane. This letter proposes a major challenge in generating three separate resonances to cover 2.16 GHz IMAT band 3.37 and 5.54 GHz WiMAX band while maintaining overall compact size of 35 × 35 × 3.175 mm 3 . Structure displays the impedance bandwidth of 3.25% (2.12–2.19 GHz), 2.06% (3.35–3.42 GHz), and 4.18% (5.40–5.63 GHz). Experimental results show that the antenna gives better radiation patterns and good antenna gains of 3.17, 5.0, and 2.2 dBi, respectively over the operating bands. Excellent agreement is obtained between measurements and simulations. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:1071–1074, 2017